MINIMISATION OF RISKS ASSOCIATED WITH THE USE OF POLLEN-BASED MEDICINES, AT THE STAGE OF POLLEN COLLECTION - A. A. Taube; T. A. Buyanova; E. I. Sakanyan (Фармация и фармакология (Пятигорск))
The aim of the study is the elaboration of Rules for Harvesting/Collecting of Pollen to minimize the risks associated with the use of pollen-based medicinal products.Materials and methods. The following electronic resources were used in the study: PubMed, Medline, ScienceDirect, Web of Science, Scopus, Google Scholar, eLibrary, World Allergy Organization, Cochrane Database, Stallergenesgreer, Allergenscienceandconsulting, Pharmacopoeia, Fda.gov, fs.usda.gov, Ema.europa.eu. The analysis covered the period from January 1, 2010 until December 31, 2021.Results. Currently, there are some general requirements for the quality of pollen in Russia, but there are no controls or standardised procedures for harvesting, drying, and purification of pollen. The USA and EU also lack established qualification programmes for pollen-collecting companies and/or individual pollen collectors. Regulatory authorities establish requirements only for visual control of raw materials or delegate responsibility to the manufacturer. The analysis of the existing regulatory documentation revealed lack of requirements for collection, storage, and processing of pollen used as the raw material for the production of allergen products. This calls for the elaboration of appropriate regulatory documents. The authors have compiled the Rules for Harvesting/Collection of Pollen, which include 6 parts. The Rules are intended for individuals directly involved in harvesting/collection of pollen, and contain requirements for pollen collectors, the process of pollen collection, documentation, storage, and transportation.Conclusion. The authors have prepared the Rules for Harvesting/Collecting of Pollen, which include 6 parts. The Rules cover the whole process of pollen collection and all related processes. The implementation of this document will improve the process of pollen collection, thus reducing the risks associated with the use of pollen-based medicines. Further studies will assess the impact of the pollen quality on the safety of medicinal products.